Biologics Beyond Boundaries: Innovative Use of Biologics in Dermatology - Abhishek De; Barnali Chowdhury; Monika Khemka; Aarti Sarda; Sudip Das (Wolters Kluwer Medknow Publications, 2021)
Several biologic agents have been approved for use in dermatology and other disciplines of medicine. However, based on the mechanism of action and a track record of the response, these agents are being increasingly used for off-label purposes to garner control of more remote and difficult disease processes. Herein, we present three difficult to treat patients where innovative uses of biologics beyond their approved indications have yielded good responses. Our first patient was a case of bullous pemphigoid, who showed excellent response to omalizumab. The second case was a patient of lepromatous leprosy with tenosynovitis and erythema nodosum leprosum, who was treated effectively with infliximab. Our third case was a treatment-resistant pyoderma gangrenosum, where infliximab showed a very good response. In the present study, we report the cases to highlight the usefulness of biologics that can expand much beyond the routine FDA approved indications.